Data governance and cross-border data flow: a comparative analysis of China, the United States, and the European Union, with a focus on TikTok and Facebook compliance - Banceviča, Jūlija (Riga Graduate School of Law, 2024)
This bachelor thesis examines two topical aspects – the legal issues and political narratives surrounding data governance governance, and mobile applications’ compliance with data protection regulations, with a focus on trans national data flow. It aims to identify the implications that arise when the personal data of mobile application users located in the European Union is stored and processed by mobile application applications located in China and the United States. By analyzing China’s and the US's developments in the field of data governance, and the compliance issues faced by two of the most widespread social media giants TikTok and Facebook , based in China and the US respectively, regarding their adherence to EU data protection regulations, this thesis presents a comprehensive overview of the challenges inherent in transnational data governance and compliance frameworks. The thesis provides a critical analysis of the suspiciosuspicions about the Chinese government's control over mobile applications and the difficulties that emerge when the personal data of mobile application users are transferred to third countries. The thesis concludes that ensuring the privacy and security of users users’ data remains a significant concern in the context of cross border data transfers involving jurisdictions with contradicting data protection standards and practices
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Data protection; data governance; Tiktok; Facebook; China; General Data Protection Regulation